2023
DOI: 10.1002/acm2.13998
|View full text |Cite
|
Sign up to set email alerts
|

SGRT‐based DIBH radiotherapy practice for right‐sided breast cancer combined with RNI: A retrospective study on dosimetry and setup accuracy

Abstract: Background: We retrospectively studied the dosimetry and setup accuracy of deep inspiration breath-hold (DIBH) radiotherapy in right-sided breast cancer patients with regional nodal irradiation (RNI) who had completed treatment based on surface-guided radiotherapy (SGRT) technology by Sentinel/Catalyst system, aiming to clarify the clinical application value and related issues. Methods: Dosimetric indicators of four organs at risk (OARs), namely the heart, right coronary artery (RCA), right lung, and liver, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Despite the widespread usage of DIBH for left-breast RT, few studies have investigated its role in right-breast cancer [23][24][25]. Some studies suggested that DIBH for right-sided breast cancer should be adopted to reduce ipsilateral lung and liver dose in loco-regional radiation therapy [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the widespread usage of DIBH for left-breast RT, few studies have investigated its role in right-breast cancer [23][24][25]. Some studies suggested that DIBH for right-sided breast cancer should be adopted to reduce ipsilateral lung and liver dose in loco-regional radiation therapy [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that DIBH for right-sided breast cancer should be adopted to reduce ipsilateral lung and liver dose in loco-regional radiation therapy [26,27]. A significant benefit was detected in reducing the maximum dose to the heart and the right coronary artery in cases of regional nodal irradiation [23,24]. Interestingly, in a study evaluating the dosimetric benefit of DIBH for locoregional irradiation of R-BC with VMAT, Loap et al concluded that adding DIBH to VMAT is not justified for all patient candidates for right-breast and regional nodal irradiation.…”
Section: Discussionmentioning
confidence: 99%